Are LAGs contributing to solving social exclusion problems? The case of Kujawsko-Pomorskie Voivodship - Kola-Bezka, Maria (Bulletin of Geography. Socio-economic Series, 2020)
The article draws on research covering all local action groups (LAGs) operating in Kujawsko-Pomorskie Voivodship. The objectives include: determining what portion of local development activities implemented by LAGs are activities for social inclusion and what their expected effects are; and determining whether LAG activities for social inclusion are adequate to the scale of social exclusion in the areas where they operate. The research demonstrates that actions against social exclusion were provided for in the strategies of 26 out of 28 LAGs and they were usually not central, but only one of several categories of planned projects. The research also revealed that in the voivodship there is no relationship between the level of threat of social exclusion in the areas where LAGs operate and the level of social inclusiveness of their strategies. It is suggested that the scale and effects of the social inclusion projects planned by LAGs are not adequate to the problems actually occurring in the areas covered by their activity.